1987
DOI: 10.1016/0014-5793(87)81013-x
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl analogs of diacylglycerol as activators of protein kinase C

Abstract: Diacylglycerols which activate protein kinase C have the 1,2‐sn configuration. Short‐chain saturated fatty acids or long‐chain unsaturated fatty acids are required for supporting the potency of these lipids. Using alkyl analogs such as 1‐O‐decyl‐2‐O‐decanoylglycerol, 1‐O‐decanoyl‐2‐O‐decylglycerol, 1,2‐O‐didecyl‐glycerol, 1‐O‐hexadecyl‐2‐O‐acetylglycerol and 1‐O‐decyl‐2‐O‐acetylglycerol, we showed that the ether bond was consistently associated with a loss of activity to varying extents. The results suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
2

Year Published

1988
1988
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 24 publications
0
14
2
Order By: Relevance
“…The fatty acid moieties involved in 1,2-DAG accumulation in tissue may not be equivalent activators of protein kinease C, since exogenous additions of 1,2-DAG and analogs have different biological potentials for activating protein kinase C (35,36). In the present study, analysis of the fatty acid composition of 1,2-DAG in the myocardium indicated no difference between the strains at the ages examined.…”
Section: Discussioncontrasting
confidence: 51%
“…The fatty acid moieties involved in 1,2-DAG accumulation in tissue may not be equivalent activators of protein kinease C, since exogenous additions of 1,2-DAG and analogs have different biological potentials for activating protein kinase C (35,36). In the present study, analysis of the fatty acid composition of 1,2-DAG in the myocardium indicated no difference between the strains at the ages examined.…”
Section: Discussioncontrasting
confidence: 51%
“…The results from that report indicate that the 1-O-alkylglycerol portion of LPG is primarily responsible for the inhibitory activity. This was not unexpected, since ether-for-acyl substitutions have been reported to result in a potent decrease in PKC-activating ability [15,16]. The type of inhibition displayed by the 1-O-alkylglycerol appears to be complex with respect to diolein concentration, since both the apparent Km and Vmax were affected.…”
Section: Discussionmentioning
confidence: 83%
“…In fact, ether-linked DG may competitively inhibit PKC activation induced by diacylglycerol species (4). Additional studies support this signaling mechanism, as ether-linked DG fail to activate total PKC activity in vitro or only activate PKC in the presence of pharmacological concentrations of calcium (5)(6)(7)(8).…”
mentioning
confidence: 99%